Analysis of Endocannabinoid System in Rat Testis During the First Spermatogenetic Wave - Migliaccio, Marina; Ricci, Giulia; Suglia, Antonio; Manfrevola, Francesco; Mackie, Ken; Fasano, Silvia; Pierantoni, Riccardo; Chioccarelli, Teresa; Cobellis, Gilda (Frontiers in Endocrinology, 2018)
Endocannabinoids are lipid mediators, enzymatically synthesized and hydrolyzed, that bind cannabinoid receptors. Together with their receptors and metabolic enzymes, they form the “endocannabinoid system”. Anandamide and 2-arachidonoylglycerol are the main endocannabinoids studied in testis. In the present study, using the first wave of spermatogenesis as an in vivo model to verify the progressive appearance of germ cells in seminiferous tubules (i.e. spermatogonia, spermatocytes and spermatids), we analyzed the expression of the main enzymes and receptors of endocannabinoid system in rat testis. In particular, the expression profile of the main enzymes metabolizing anandamide and 2-arachidonoylglycerol as well as the expression of cannabinoid receptors, CB1 and CB2, and specific markers of mitotic, meiotic and post-meiotic germ cell appearance or activities have been analyzed by RT-PCR and appropriately correlated. Our aim was to envisage a relationship between expression of endocannabinoid system components and temporal profile of germ cell appearance or activity as well as among ECS components. Results show that expression of endocannabinoid system components is related to germ cell progression. In particular, CB2 and 2-arachidonoylglycerol appear to be related to mitotic/meiotic stages while CB1 and anandamide appear to be related to spermatogonia stem cells activity and spermatids appearance, respectively. Our data also suggest that a functional interaction among endocannabinoid system components occurs in the testis. Indeed in vitro-incubated testis show that AEA-CB2 activity affects negatively MAGL levels via up-regulation of CB1 suggesting a CB1/CB2 mediated-relationship between AEA and 2-AG. Finally, we provide the first evidence that CB1 is present in fetal gonocytes, during mitotic arrest.